(untitled) (Research, Society and Development, 2022)
In order to overcome known barriers and link rural scenarios to health services, the work of Primary Health Care - PHC, in the proposition of knowing the reality in which people with disabilities are inserted is part of the work process. This study aims to report the experience of a member of a family health strategy team and reveal the reality of people with disabilities regarding access to the local health service. This is a qualitative, descriptive study, of the experience report type, developed in a basic health unit located in the rural area of ​​Petrolina-PE, from the identification through the analysis of the epidemiological profile and the sharing of the experience with people with disabilities in the territory ascribed by the family health strategy, and who were attended by the family health team, located in the rural area of ​​the municipality of Petrolina, during the months of December 2020 to May 2021. Regarding the physical structure, it was found that the reception requirements for people with disabilities were not met, due to the lack of accessibility to the interior of the health units. It is recommended that physical facilities be accessible and properly allocated to support the most vulnerable and disadvantaged segments of the population, in order to include people with disabilities in primary health care. It is therefore essential that services are organized to respond to these demands.